Protective role of alpha-tocopherol on retinal injury in experimental uveitis in guinea pigs - Demir, Dilek; Yilmaz, Turgut; Ilhan, Nevin; Yekeler, Hayrettin; Aydemir, Orhan; Kükner, A.Şahap (My University, 2006)
Purpose: Purposeof the study was to determine whether alpha-tocopherol (AT) can protect the retina from oxidative damage in experimental uveitis (EU). Material and Methods: The eyes of 36 adult male guinea pigs were studied. The guinea pigs were divided into three groups of 12 animals each. The first group was used as control. The right eyes of groups 2 and 3 received an intravitreal injection of bovine serum albumin for EU induction. At the same time and also on the consecutive third and fifth days, group 3 received intraperitoneal AT injections. The samples were collected on the eighth day. Retinal malondialdehyde (MDA) levels and the average thickness of the inner plexiform layer were measured and the histopathology of the eyes was studied. Results: The MDA level was significantly lower in the control group than in the groups 2 (p < 0.01) and 3 (p < 0.05). When compared with the EU group 2, there was a significant lowering of MDA in the AT injected group 3 (p < 0.01). The thickness of the inner plexiform layer in the control group 1 was significantly lower than in the other groups (p < 0.01). Its thickness in the group 3 supplied with AT was significantly lower than in the group 2 (p < 0.01). Conclusions: The data indicate that intraperitoneal AT administration protects against EU injury in the guinea pig retina as evidenced by the reduced MDA and the thickness of retina. © 2006 Elsevier Ireland Ltd. All rights reserved.
Keywords: Alpha-tocopherol; Experimental uveitis; Lipid peroxidation; Retina